Pemberdayaan Perempuan Melalui Pelatihan Menjahit dalam Peningkatan Keuangan Keluarga - Westim Ratang; Mery Pegome; Perakwati Munte (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2023)
The purpose of this service is to empower women by providing knowledge, motivation, and sewing skills for women members of the PELWAP Eben Haezer Kotaraja to be able to increase family finances by opening a sewing business. The method used is face-to-face and practice. The results of the dedication show that it is necessary to carry out sewing training activities on an ongoing basis to improve the ability of female members of the PELWAP Eben Haezer Kotaraja.